Adaptive and Transformational Leadership During Crisis: A Case Study of a Junior High School in Yogyakarta - Farid Setiawan; Nurwanto Nurwanto; Hanif Cahyo Adi Kistoro; Wajiran Wajiran (AL-ISHLAH: Jurnal Pendidikan, 2025)
The COVID-19 pandemic posed significant challenges for private schools in Indonesia, particularly in terms of financial stability, declining student enrollment, and weakened institutional management. This study investigates how adaptive and transformational leadership was implemented to manage crisis conditions at Muhammadiyah Junior High School 10 (SMP Muhdasa) in Yogyakarta, with a focus on the leadership practices of a newly appointed female principal. Using a qualitative descriptive approach, data were collected through field observations, in-depth interviews with the principal, and analysis of school documents between January and March 2024. The data were analyzed using Gadamerian hermeneutics to explore leadership strategies in a crisis context. Findings show that the principal employed adaptive and transformational leadership marked by participatory communication, strategic decision-making, and stakeholder engagement. Internally, the school’s resilience was supported by a strong organizational culture, inclusive team dynamics, and spiritual motivation. Externally, collaboration with Muhammadiyah networks, parents, and community stakeholders played a crucial role in supporting the school’s recovery and innovation efforts. The study highlights that effective crisis leadership is not only managerial but also deeply rooted in value-based, inclusive, and collaborative approaches. The principal's integration of spiritual values, philanthropic programs, and digital transformation fostered institutional resilience. This case provides a reference model for school leaders navigating educational crises through adaptive and transformational leadership.